ANALISIS TENTANG PELAKSANAAN KUDA LUMPING YANG DIMAINKAN OLEH ANAK-ANAK DI KEPENGHULUAN MUKTI JAYA KECAMATAN RIMBA MELINTANG KABUPATEN ROKAN HILIR - Darsono, Darsono; Erlinda, Sri; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the implementation of kuda lumping phenomenon in which there are children. Children are involved in the appearance of kuda lumping to maintain the existence and preservation of kuda lumping, kuda lumping loaded with violence and magic usually played by adults, but in this case children who are mentally and physically not ready for things related to the element of violence and the magic. Kuda lumping is also always held at night until late at night. This phenomenon raises the perception or response of the community of Village Mukti Jaya. So the authors take a study entitled